Risk factors associated with higher WHO grade in meningiomas: a multicentric study of 552 skull base meningiomas - Michaela May; Vojtech Sedlak; Ladislav Pecen; Vladimir Priban; Pavel Buchvald; Jiri Fiedler; Miroslav Vaverka; Radim Lipina; Stefan Reguli; Jozef Malik; Martin Cerny; David Netuka; et al. (Scientific Reports)
Abstract The histological grade is crucial for therapeutic management, and its reliable preoperative detection can significantly influence treatment approach. Lacking established risk factors, this study identifies preoperative predictors of high-grade skull base meningiomas and discusses the implications of non-invasive detection. A multicentric study was conducted on 552 patients with skull base meningiomas who underwent primary surgical resection between 2014 and 2019. Data were gathered from clinical, surgical and pathology records and radiological diagnostics. The predictive factors of higher WHO grade were analysed in univariate analysis and multivariate stepwise selection logistic regression analysis. Histological analysis revealed 511 grade 1 (92.6%) and 41 grade 2 (7.4%) meningiomas. A prognostic model predicting the probability of WHO grade 2 skull base meningioma (AUC 0.79; SE 0.04; 95% Wald Confidence Limits (0.71; 0.86)) based on meningioma diameter, presence of an arachnoid plane and cranial nerve palsy was built. Accurate preoperative detection of WHO grade in skull base meningiomas is essential for effective treatment planning. Our logistic regression model, based on diameter, cranial nerve palsy, and arachnoid plane, is tailored for detecting WHO grade 2 skull base meningiomas, even in outpatient settings.